The Obstacles of Women Entrepreneurship on Empowerment in Rural Communities KwaZulu Natal, South Africa - Aliamutu, Kansilembo Freddy; Mkhize, Msizi Vitalis (CV. Literasi Indonesia, 2024)
This research aims to determine barriers to the expansion of women-owned businesses in rural communities of South Africa. To collect data for the research, a quantitative research approach was adopted. The research focused on 250 female business owners in the northern KZN rural regions of Umzinyakude, Uthukela, and Ugu. According to the survey, the primary barriers to developing women-owned businesses in rural communities are financial restraints, an absence of formal education, and inadequate facilities. These hurdles, however, may be overcome by women businesses being entrepreneurs in rural South African communities. Eliminating these barriers might empower women entrepreneurs and drive growth in the economy in rural communities, lowering poverty and improving rural people's living conditions. In light of these findings, the research suggests a variety of measures, including different financing methods, focused training and schooling programs, and the development of infrastructure to help women-owned businesses flourish in rural communities. Further research should investigate more issues like cultural as well as social barriers, an absence of accessibility to marketplaces and information, and legal and regulatory obstacles that prevent women from starting business entities in rural communities.